AN ANALYSIS OF LANGUAGE STYLE IN “TO ALL THE BOYS I’VE LOVED BEFORE” MOVIE - Alicia Febriani; Fakhri Ras; Novitri Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Language Style is the formality construct of the language used tocommunicate with other people. This study aims to analyze the types of language style used and the dominant type used in “To All The Boys I’ve Loved Before” movie. The movie is classified as a young-adult romantic movie directed by Susan Johnson and was released on August 17 2018 on Netflix. The source of the data was taken from the script of “To All The Boys I’ve Loved Before” movie. The research design is a descriptive qualitative research. The analysis is based on the five language styles adopted from Martin Joos’ (1976) theory; they are frozen style, formal style, consultative style, casual style and intimate style. The result shows that there are thirty (30) data from the conversation in the movie to perform the language styles. The collected data can be concluded that the type of style occurs dominantly in the movie is intimate style. The thirty cases comprise of intimate (eleven cases), consultative (nine cases), casual (sevencases), formal (three cases) and frozen (none) style. This means that intimate style is prominently proved to be used in communication within family relation and close friends. Based on the result of the study, it is fruitful to suggests the students of English Department to do further analysis about the five language styles used in other resources like movies, novels, or articles.Key Words: Language Style, Movie, To All The Boys I’ve Loved Before